THU0380 Increased Expression of Bruton Tyrosine Kinase in Patients with Lupus Nephritis and its Clinic Significance. (9th June 2015) - Kong, W.; Deng, W.; Feng, X.; Yao, G.; Chen, W.; Tang, X.; Sun, Y.; Huang, S.; Zhang, Z.; Shi, B.; Sun, L.
Abstract : Background: Systemic lupus erythematosus (SLE) is an autoimmune disease manifested by multiorgan impairment including glomerulonephritis, cutaneous lesions and arthritis. B cells participate in the onset of SLE. As a downstream signaling molecule of B-cell receptor (BCR) signaling pathway, Bruton tyrosine kinase (Btk) is involved in the development, activation and survival of B cells. It is reported that transgenic mice overexpressing Btk specifically in B cells could produce antinuclear antibody and develop a lupus-like symptoms. Objectives: The aim of our study was to identify the specific role of Btk in lupus nephritis. Methods: The percentages of Btk positive CD19+ B cells from 28 SLE patients and 28 healthy donors were examined by flow cytometry. The correlation between the percentages of Btk positive CD19+ B cells and some lupus related clinical indicators were analyzed. Immunohistochemistry was used to detect the Btk expression in kidney biopsies from 8 lupus nephritis (LN) patients and 8 controls. The levels of Btk expression in glomerulus were detected by image-pro plus analysis, and represented by mean optical density (MOD). Results: The frequency of Btk+CD19+ B cells from SLE patients is up-regulated compared with the healthy controls (3.89±0.31 vs 2.61±0.21, p <0.01), significantly correlating with the SLE activity (SLEDAI) (r=0.53), levels of serum anti-dsDNA antibody (r=0.41), levels of serum C3 (r=-0.41), and the amount of 24 hours urine protein (r=0.59). We also found that the frequency of Btk+CD19+ B cells in the patients with lupus nephritis was significantly higher compared with the patients without lupus nephritis (4.71±0.481 vs 3.19±0.30, p <0.05). The levels of Btk expression in glomerulus were markedly increased in LN patients compared with controls (0.04±0.01 vs 0.01±0.00, p <0.001). Conclusions: Btk expression is significantly increased in LN, which may be a promising therapeutic target for the molecular therapy of SLE. Disclosure of Interest: None declared